Kontribusi Ikhtilaf serta Penerapannya pada Masyarakat - Arya Bagus Setiawan; Ahmad Mu’is; Muhammad Miftakhul Munir; Muhamad Havidz Davala (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2025)
This study aims to identify and understand the meaning of ikhtilaf, its types, the causes of its emergence, and its implications for society. This study is a qualitative study, the data source is through library research. The data analysis uses thematic analysis methods, descriptive as a stage of studying texts, messages, instructions or information from primary and secondary sources, then confirmed by one source with another holistically towards a general conclusion. The results of this study indicate that the application of ikhtilaf in society, especially in countries with plural populations, requires an attitude of mutual respect and tolerance. In this context, ikhtilaf can be a means to create a diversity of productive thoughts, as long as it is accompanied by the principles of ukhuwah (brotherhood) and good adab (ethics). A society that is able to understand and accept ikhtilaf will be more open to dialogue, encourage understanding in differences, and maintain social harmony. Therefore, the application of ikhtilaf in society not only has the potential to enrich collective insight, but also strengthen social cohesion based on the principles of justice, mutual understanding, and unity in diversity.